Restitution as a Form of Legal Protection for Child Victims of Sexual Violence with Perpetrators of a Biological Father Based on the Principles of Justice - Wardhani, Devita Wisnu; Mulyanto, Mulyanto (Technium Social Sciences Journal, 2023)
Criminal cases in Indonesia cannot be seen from one side only, namely the fate of the perpetrators themselves. However, there are several things that need to be considered when it comes to victims of crime, this is because the victim suffers material and non-material losses and this is also legal protection for the victim.One of the rights regulated by law is the right to protection against sexual violence. In this research the problem isCan restitution be used as a form of legal protection for child victims of sexual violence by biological fathers based on the principle of justice? Then the method usedis a qualitative research, namely a research method that emphasizes the aspect of in-depth understanding of a problem rather than examining the problem in general, which uses in-depth analysis techniques, namely examining problems case by case in this case cases that occurred in the District Court Salatiga. The result is that restitution can be used as a form of legal protection for child victims of sexual violence, including if the perpetrator is the victim’s own father. However, it is still necessary to receive criticism and input that there is no specific law that regulates this right to restitution, including if the perpetrator is the biological father of the victim, so this creates various kinds of problems and ambiguity at the implementation level.